Status of stone weevil, Aubeus himalayanus Voss (Curculionidae: Coleoptera) in India: An emerging pest of ber (Ziziphus mauritiana Lamk) (Indian Journal of Arid Horticulture, 2013)
The Indian jujube, popularly known as ber(Ziziphus mauritiana Lamarck), is an important fruit crop grown in arid  and semi arid regions of India and worldwide. Nutritionally, the fruits are rich in protein, phosphorus, calcium, carotene and  vitamin C. In India, there are various factors responsible for yield losses in terms of quantity as well as quality. Of these, biotic  stresses such as pests and diseases are of prime importance. Among the various insect-pests infesting ber, the stone weevil Aubeus himalayanusVoss (Curculionidae: Coleoptera) seems to be is a new threat to ber cultivation in India as in recent years  severe infestation has been reported in different ber growing region viz., Anantapur (Andhra Pradesh), Rahuri (Maharashtra),  Jobner (Rajasthan), Bijapur (Karnataka) and Bikaner (Rajasthan). In addition, the infestation of this pest was also reported  from Bangladesh. The adult female weevil, characterized by dark brown snout, usually lays eggs on the stylar end of fruits  and rarely on the distal end. The newly emerged white colour grubs enter into seed by making puncture in endocarp at  immature stage and starts feeding on soft seed coat. Later it enters into endosperm moving downward and starts feeding upon  inner content of the seed, and pupates within the seed by making hallow galleries. The weevil completes its life within a single  fruit. The infestation results in severe fruit drop at initial stage of fruit set. The damage intensity of stone weevil varies with  cultivars as varieties with larger stone are preferred over those, which have higher pulp content. Periodical monitoring of  orchard for weevil incidence is essential for devising suitable strategies for efficient management of pest in time. Detection at  advance stages of infestation would render it difficult to manage as pests enters into the seed.
Keywords: Ziziphus mauritiana; stone weevil; Aubeus himalayanus